PENGEMBANGAN BUKU PANDUAN PRAKTIK LABORATORIUM BANK MINI DALAM RANGKA MENINGKATKAN KETERAMPILAN PENCATATAN TRANSAKSI KEUANGAN PADA PROGRAM KEAHLIAN AKUNTANSI - Mulasiwi, Cut Misni; M.Stats, Siswandari; Santosa, Djoko (Jurnal Pendidikan Insan Mandiri, 2016)
The objective of this research is to develop a valid and effective guidance book for practice to be applied at Mini Bank laboratory of the Accounting Expertise Program of State Senior Vocational High School 1 of Surakarta as to improve the skills of financial transaction recording.This research used the research and development (R&D) method claimed by Borg and Gall. It consisted of eight phases of development, namely: (1) research and information collecting, (2) planning, (3) development of preliminary form of product, (4) preliminary field testing, (5) main product revision, (6) main field testing, (7) operational product revision, and (8) operational field testing. The validation of product was done through internal and external ones. The former was done to the components of developed book through peer review which involved a material expert, a media expert, two practitioners, namely the teachers who develop the mini bank of the school. Meanwhile, the latter was done by testing the feasibility of the developed book which involved the students in Grade X and Grade XI of the Accounting Expertise Program of the school. The research methods used in the testing implementation was the descriptive qualitative and quantitative one.The results of research show that: (1) the developed guidance book for practice of mini bank laboratory is valid and feasible to be used according to the result of validations by experts and that of testing by students; (2) the developed guidance book for practice of mini bank laboratory is proven to be effective to be applied as a reference for practical learning activities so that it can improve the skills of financial transaction recording of the students of the school. Thus, a conclusion is drawn that the developed guidance book for practice of mini bank laboratory is valid and effective to improve scores in the skills of financial transaction recording of the students in Grade X and XI of the Accounting Expertise Program of State Vocational High School 1 of Surakarta.  Keywords:Guidance book, practical learning, mini bank laboratory, vocational